Originally Posted by

**SuperCalculus** There's a much easier way.

You're working with a circle with equation with equation $\displaystyle x^2 + y^2 + 2gx + 2fy + c = 0$, where centre is $\displaystyle (-g, -f)$ and radius is $\displaystyle \sqrt{g^2 + f^2 - c}$

So, from the equation you gave, you can derive;

$\displaystyle -10x = 2gx$

and

$\displaystyle 4y = 2fy$

Hence;

$\displaystyle g = -5$

$\displaystyle f = 2$

So, plug those values into the equations

Centre is $\displaystyle (5, -2)$

And radius is $\displaystyle \sqrt {25 + 4 - 13} = \sqrt {16} = 4$.